Prevalence of Depression in Patients with Parkinson’s Disease (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Parkinson’s disease is among most frequently encountered neurological disorders by neurologists. It has a varied spectrum of symptoms and presenting complaints. An important part of this disease is associated depression being commonly seen in these patients. Objectives: To Determine The Prevalence Of Depression In Patients Having Parkinson’s Disease. Materials and Methods: This study was a cross sectional survey which was conducted at department of Neurology Services Hospital, Lahore over a period of 3 months. A total 114 cases were recruited in this study after informed consent. For evidence of depression, a questionnaire was used as a data collection tool and score was given using beck depression inventory-ii (BDI-ii) criteria. All collected data was entered into SPSS 21 version and was analyzed. In our study descriptive analysis qualitative and quantitative variables were seen. Results: We found that mean age of the patients was 60.75 ± 9.06 years. Also mean age of onset of disease was found as 55.6 ± 3.84 years. We found that 48 patients (42.1%) in our study were normal according to BDI-ii criteria. Fourteen patients (12.2%) had mild mood disturbance; 19 patients (16.6%) had borderline clinical depression; 15 (13.1%) had moderate depressive mood; 15 patients (13.1%) had severe depressive mood; and 3 patients (2.6%) had extreme depression. The overall prevalence of depression was calculated as 54.3% in our study. Conclusion: Depression is present in significant number of patients presenting with Parkinson’s disease. So it is advised to do psychiatric evaluation of all patients with Parkinson’s disease for early detection and proper management.
Keywords: Parkinson’s Disease; Depression; Prevalence